Editorial for the Special Issue Entitled “Carbon-Based Quantum Dots” - Su Chen (Nanomaterials, 2023)
Carbon-based quantum dots, also known as carbon dots (CDs), are a unique class of carbon-based nanoparticles with sizes below 10 nm [...]